The Effect of Pegagan (Centella Asiatica (L.) Urban) Ethanol Extracts on Hippocampal PSD-95 Protein Expression in Male Wistar Rats - Adibah Ferhad; Auliyani Andam Suri; Astri Handayani; Sri Redjeki; Ria Kodariah (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
One effort to overcome the decline in memory function is through herbal medicine. Pegagan (Centella asiatica (L.) Urban) contain the active components of triterpenoid and flavonoids, has been known to be able to improve memory function. Synaptic plasticity is the basis of memory formation which is strongly influenced by synapse proteins such as PSD-95. Loss of PSD-95 protein can cause memory function decline. This study aims to determine the effect of 70% ethanol extract of pegagan toward PSD-95 protein expression on hippocampus of male Wistar rat. Eighteen male Wistar rats were randomly divided into 3 groups, 6 rats/group: group (1) given ethanol extract of pegagan with dose 300 mg / kgBW / day (CA300), (2) given ethanol extract of pegagan with dose 600 mg / kgBW / day (CA600), and (3) control group (K), given daily aquadest. All three groups were treated for 28 consecutive days. At the end of the treatment period, rats were decapitated and the hippocampus was isolated from the brain. Analysis of protein was done by immunohistochemical method. Statistical analysis was performed by One Way ANOVA parametric test followed by Post-Hoc Bonferroni. The results showed that there was no significant difference between group K and group CA300 (P = 0.123), whereas there were significant differences between CA600 group and K group and CA300 group (P = 0.000). From this research, it can be concluded that 70% ethanol extract of pegagan with dose 600mg / kgBW / day can increase expression of PSD-95 protein on hippocampus of male Wistar rat.